MICRO, SMALL, AND MEDIUM ENTERPRISES PERFORMANCE: FINANCIAL MANAGEMENT AS MODERATION - Wulandari, Ika (Kesatuan Press, 2025)
This study aims to determine the effect of financial literacy, financial inclusion, and financial Management on the performance of MSMEs. This study is a type of quantitative research. The population of this study is all MSMEs in the Sleman Regency. The research sample was obtained using the Slovin formula with a purposive sampling method and a margin of error of 10%. The number of samples was 100 people. This study used primary data and questionnaires to collect data. Data analysis in this study used the Smart PLS program. The study results indicate that Financial Literacy affects the Financial Performance of Sleman Regency. Financial Inclusion Affects the Financial Performance of MSME Actors in Sleman Regency. Financial Management Does Not Affect the Financial Performance of MSME Actors in Sleman Regency. Financial Management does not strengthen financial literacy on financial performance. Financial Management does not reinforce financial inclusion in the financial performance of MSME actors in the Sleman Regency. The implication of the results of this study is the importance of improving financial literacy through training or mentoring programs to increase awareness of the risks faced if financial literacy is low, such as poor debt management or misinvestment—the importance of seeking information about financial products that suit your business needs.